A new species of the genus Metacrangonyx (Crustacea: Amphipoda) from the ground waters of Morocco, with comparisons to all other species in the genus - Elassad, Nabila; Messouli, Mohamed; Boulal, Mokhtar; Boudellah, Abderrazzaq; Ghamizi, Mohamed (Zootaxa, 2025)
Description of a new species of the genus Metacrangonyx Chevreux, 1909 from Moroccan groundwaters. This new species Metacrangonyx boutini sp. nov. is found in the underground waters of the Tiznit plain in southeastern Morocco and adds to the diversity of the Metacrangonyctidae in the Mediterranean and especially in Morocco. In this species antenna 1 reaches 64% of body length, with the first peduncular article bearing a sternodistal robust seta; an accessory flagellum formed of four articles slightly longer than half the third article of the main flagellum; a short antenna 2, about 1/3 the length of antenna 1 and never reaching half its length. This species can be distinguished from other Metacrangonyx species by a short, wide peduncle of uropod 3, without robust seta, but with a simple seta on the inner surface; a very short globular endopodite bearing a small robust seta; and a slightly elongated exopodite with two apical and one or two parietal robust setae.